2009
DOI: 10.1098/rspb.2009.0051
|View full text |Cite
|
Sign up to set email alerts
|

Is there an adverse effect of sons on maternal longevity?

Abstract: Recent years have witnessed the emergence of a literature examining the effects of giving birth to sons on postmenopausal longevity in pre-industrial mothers. The original paper in this lineage used a sample (nZ375) of Sami mothers from northern Finland and found that, relative to daughters, giving birth to sons substantially reduced maternal longevity. We examine this hypothesis using a similar and a much larger sample (nZ930) of pre-industrial Sami women from northern Sweden, who in terms of their demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 19 publications
1
28
1
Order By: Relevance
“…This finding supports the hypothesis that energetic resources invested in reproduction by the mothers may compromise those resources available for longevity (Kirkwood & Rose 1991). Using similar but a larger dataset of Sami mothers from Sweden, a neighbouring country of Finland, Cesarini et al (2009) found no evidence for the association between sons born and the mothers' post-menopausal lifespan. The authors made two main conclusions: (i) our results were likely to be false-positive because of smaller sample size and (ii) that current evidence for the association between offspring sex and maternal longevity is rare and restricted to these Finnish Sami only.…”
Section: Published Insupporting
confidence: 71%
See 4 more Smart Citations
“…This finding supports the hypothesis that energetic resources invested in reproduction by the mothers may compromise those resources available for longevity (Kirkwood & Rose 1991). Using similar but a larger dataset of Sami mothers from Sweden, a neighbouring country of Finland, Cesarini et al (2009) found no evidence for the association between sons born and the mothers' post-menopausal lifespan. The authors made two main conclusions: (i) our results were likely to be false-positive because of smaller sample size and (ii) that current evidence for the association between offspring sex and maternal longevity is rare and restricted to these Finnish Sami only.…”
Section: Published Insupporting
confidence: 71%
“…Based on their larger sample size and non-significant results, Cesarini et al (2009) seem to suggest that our findings were false-positive. Our original publication was based on all Sami women resident in three Finnish Sami populations between 1640 and 1870, but we were unable to include all these women in our analysis because of missing records on their age at death.…”
Section: Published Inmentioning
confidence: 81%
See 3 more Smart Citations